Antimicrobial activity of cefmetazole (CS-1170) and recommendations for susceptibility testing by disk diffusion, dilution, and anaerobic methods. - Jones, R N (1986)
Cefmetazole, formerly CS-1170, was found to have antimicrobial activity slightly superior to that of cefoxitin but a clinically usable antimicrobial spectrum that should be considered identical to that of cefoxitin. Disk diffusion and dilution test methods with cefmetazole correlated highly (r, greater than or equal to 0.95) with cefoxitin results. The recommended 30-micrograms cefmetazole disk interpretive breakpoints for susceptibility and resistance were greater than or equal to 18 mm (MIC, less than or equal to 8.0 micrograms/ml) and less than or equal to 14 mm (MIC, greater than or equal to 32 micrograms/ml), respectively. Cefmetazole and cefoxitin should be considered to be in the same antimicrobial spectrum class, requiring separate testing for other cephalosporins such as cephalothin, cefamandole, cefuroxime, and cefotetan. Recommended interpretive criteria performed well for fastidious organisms (Haemophilus influenzae, Neisseria meningitidis, and Branhamella catarrhalis) and for broth microdilution tests with anaerobes. Cefmetazole and cefoxitin broth disk elution tests for anaerobic bacteria produced higher rates of false susceptibility results.